Effects of 4 weeks of ß-alanine supplementation on aerobic fitness in water polo players - Motta Pinheiro Brisola, G.; Redkva, P. E.; Muller Pessôa Filho, D.; Papoti, M.; Moura Zagatto, A. (PLOS ONE, 2018)
The purpose of the present study was to investigate the ergogenic effects of 4 weeks of ß-alanine supplementation on peak oxygen uptake () and force associated with () during a tethered swimming graded exercise test, and a three-minute all-out effort (3minALL-OUT) in water polo players. Twenty-two male national competitive level water polo players were randomly assigned to receive either 4 weeks of ß-alanine (n = 11) or a placebo (n = 11) (i.e., 4.8 g·day-1 for 10 days, then6.4 g·day-1 for 18 days, resulting in 163.2 g over 28 days). The participants performed the TSGET and 3minALL-OUT before and after the supplementation period. There were no significant interaction effects between-groups for any variable, however, the magnitude-based inferences analyses showed a possibly beneficial effect (74%) of ß-alanine supplementation on compared to placebo treatment (% [post-pre] for Placebo group = -5.2%; % [post-pre] for ß-alanine group = +0.7%). Only the ß-alanine group presented a significant reduction in expressed in absolute values (PRE = 3.3±0.6L·min-1; POST = 3.0±0.4L·min-1; p = .021). Similarly, only the ß-alanine group presented a significant increase in critical force (PRE = 51.2±10.4N; POST = 56.5±13.1N; p = .044) and a reduction in the curvature constant parameter (W'; PRE = 2998.0±1103.7N·s; POST = 2224.6±1058.9N·s; p = .049). Thus, we can conclude that 4 weeks of ß-alanine supplementation presented mixed results in water polo players, indicating that this nutritional strategy may not be effective in improving parameters of the TSGET and 3minALL-OUT .